Information interventions and social media - Giovanni Gregorio; Nicole Stremlau (Internet Policy Review, 2021)
Recent conflicts, particularly in Asia and Africa, have highlighted the potential for social media to provoke or exacerbate violent conflict and mass atrocities. The role of media and propaganda in disseminating hate and violence has been a longstanding aspect of war. In some cases of violent conflict, international actors-including the United Nations (UN)-have undertaken 'information interventions', a term that came into its own in the mid-1990s in response to the ongoing conflict in the Balkans, and the use of radio in the Rwandan genocide in 1992. While information intervention has historically been applied to mass media, this article explores the relevance and applicability of this approach to online communications, and social media in particular. We unpack whether and how information intervention might apply when social media has a role in inflaming extreme violence, or genocide, by disseminating disinformation and hate speech and international actors have a responsibility to protect and halt mass atrocities.
Keywords: 300; Social media; Hate speech; Content moderation; Conflicts; Responsibility toprotect